The cellular landscape of the normal kidney allograft: Main players balancing the alloimmune response - McDaniels, Jennifer M.; Shetty, Amol C.; Rousselle, Thomas V.; Bardhi, Elissa; Maluf, Daniel G.; Mas, Valeria R. (Frontiers in Transplantation, 2022)
Despite recent scientific advances made in short-term outcomes, minimal improvements have been observed in long-term kidney transplantation outcomes. Due to an imbalance between organ transplant availability and patient waiting list, expanding kidney allograft longevity is a critical need in the field. Prior studies focused on early ischemic or immunological conditions affecting kidney allografts (i.e., delayed graft function, acute rejection) or after chronic injury is established when interventions are no longer feasible. However, there are no studies exploring cellular distribution, cellular interactions and associated pathways that characterize kidney allografts with normal function. Herein, we used single nuclei RNA-sequencing to uncover the cellular landscape and transcriptome of the normal kidney allograft. We profiled 54,810 nuclei from 7 human kidney biopsies (normal native, N=3; normal allograft, N=4); normal allograft protocol biopsies were collected ≥15-months post-transplant. A total of 17 distinct cell clusters were identified with proximal tubules (25.70% and 21.01%), distal tubules (15.22% and 18.20%), and endothelial cells (EC) (4.26% and 9.94%) constituting major cell populations amongst normal native and normal allograft kidneys, respectively. A large proportion of cycling cells from normal native kidneys were in G1-phase (43.96%) whereas cells from normal allograft were predominantly in S-phase (32.69%). This result suggested that transcriptional alterations between normal native and normal allograft biopsies are predicated on the new host environment, immunosuppression, and injury-affliction. In the normal allograft, EC-specific genes upregulated metabolism, immune response, and cellular growth, emphasizing their role in maintaining homeostasis and tissue-specific stress response. Notably, we detected 6 immune subclusters in the normal allograft comprised of B (2.81%), macrophages (24.96%), monocytes (15.29%), natural killer (NK) (12.83%), neutrophils (8.44%), and T cells (14.41%) driving the alloimmune response. Phenotypic characterization of immune cell markers indicated lymphocyte activation and proinflammatory cytokines signaling pathways (IL-15, IL-32). B, NK, and T cell activation are potential mechanisms underlying subclinical inflammation and repair. These single nuclei analyses provide novel insights into kidney and immune cell associated signaling pathways that portray kidney grafts with normal allograft function beyond 2-years post-transplant; understanding the normal allograft kidney transcriptomic signatures at single cell resolution is critical for extending graft survival.